Estudo experimental e de simulação da fluidodinâmica de um leito de jorro com tubo Draft - Vieira Neto, José Luiz (2007)
The spouted bed has been used in several processes as drying, granulation, catalytic polymerization, residues treatment and materials coating. This application is due to the excellent fluid-particle contact and to the characteristics of the solids circulation. In spite of its extensive application, the spouted bed has some scale-up limitations, so it s necessary a better understanding about its fluid dynamic behavior. So, the knowledge of fluid and particles flows inside the spouted bed is of great interest for this equipment project, although the quantification of the solids motion is difficult to measure, even in regions of smaller density as in the spout. Another limitation presented by the conventional configuration of the spouted bed is the "short-circuit" of particles, in other words, the return of the particles that are in the spout-annulus interface for the spout before traveling the whole annulus area. This shortcircuit provokes a larger distribution of particles residence time, resulting in a heterogeneous product. An alternative to outline this limitation is to introduce a central tube (draft) that besides preventing this problem can also significantly alter the fluid dynamic of the bed, bringing other relative consequences to the fluid-particle contact. In the Computational Fluid Dynamic (CFD) modeling of two-phase gas-solid flows the drag force is one of the principal forces that acts in the particles, and has an important paper in the coupling among the two phases. Besides, in the spouted bed, the solids volume fraction can vary of practically zero to the maximum value of the packing limit, taking to a much more compound behavior of drag force than in conventional fluidized systems. So, it s necessary a special care in the choice of the drag model that best describes the multiphase flows studied. Among the drag models analyzed in the present work, the model of GIDASPOW et al. (1992) shows the best agreements with experimental data in the minimum spout condition. In this work, the fluid dynamics characteristic profiles of the spouted bed with and without draft tube were simulated by the CFD technique, through a Multiphase Granular Eulerian Model, using soybean seeds as particulate material. The characteristic curves of pressure drop in function of the air flow simulated, for the different configurations of the spouted bed (conventional and with tube draft located at different distances of the base), were compared with the experimental data presenting good agreement. Besides, were obtained simulated profiles of void in the spout area and of particle velocity in the annulus for air flows 20% higher than experimental minimum spout condition of each configuration (Q=1,2QJM exp). Finally was made an analysis of the influence of the distance of the draft to the base (Hd) on the air velocity simulated profiles in the spout areas and to annulus for a same feeding air flow.